Case Report: A rare chromosomal imbalance with dup 7q36.3-qter and del 7pter-p22.3 arising from parental pericentric inversion - Lin, Rongbo; Zhang, Wenhui; Huang, Mingwei; Shen, Yansheng; Liao, Jianxiang; Song, Ping; Qi, Ying; He, Jie; Xia, Yuanxiang; Duan, Jing; Ye, Yuanzhen; Yi, Qiuwei; et al. (Frontiers in Genetics, 2025)
Chromosomal abnormality is a significant cause of neurodevelopmental delay and congenital malformation. Only a few cases of chromosome 7 imbalances with both duplication of the distal long arm (7q) and deletion of the distal short arm (7p) have been reported without a systematic analysis of the genotype-phenotype relationship. We identify a new case of chromosome 7 imbalance with dup 7q36.3-qter and del 7pter-p22.3 and thoroughly characterize the chromosomal abnormality in the patient and related family members using a variety of genetic tests. More importantly, similar cases of 7q duplication and 7p deletion arising from parental pericentric inversion are reviewed to clarify the genotype-phenotype correlation of the disease. In summary, in cases of normal prenatal and early postnatal growth, progressive neurodevelopmental delay, intellectual disability, limited speech, and mild facial dysmorphism, the rare combination of duplication and deletion of distal ends of chromosome 7 may be suspected. Parental pericentric chromosomal inversion is likely a genetic contributor to the duplication-deletion imbalance in the offspring despite normal phenotypes in the inversion carrier, so genetic testing and counseling are recommended for better disease management and prevention.